2020
DOI: 10.2118/197371-pa
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Permeability and Strain Evolution in Chemical Creep Compaction Experiments with Fractured and Unfractured Chalk Cores Conducted at Reservoir Conditions

Abstract: Summary Understanding the effect of typical water-related improved oil recovery techniques is fundamental to the development of chalk reservoirs on the Norwegian Continental Shelf (NCS). We investigate the contribution and interplay of key parameters influencing the reservoir's flow and storativity properties, such as effective stresses, injecting fluid chemistry, and geomechanical deformation. This is done by developing a mathematical model that is applied to systematically interpret experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The routine part of the toolbox comprises: All noted methods are positively tested, and detailed methodology recipes exist for chalk [5,6,10,32], ready for application within analytical routines for applied research within the hydrocarbon industry and here focussed on EOR research. The toolbox is designed to enable selecting the quickest and most economic tools to yield necessary datasets for decision making and modelling in this field of HC research and industrial applications (e.g., [5,42]). This concept stresses the need of valuable mineralogical input for simulators to be able to upscale from pore-to core-and field-scale.…”
Section: Discussionmentioning
confidence: 99%
“…The routine part of the toolbox comprises: All noted methods are positively tested, and detailed methodology recipes exist for chalk [5,6,10,32], ready for application within analytical routines for applied research within the hydrocarbon industry and here focussed on EOR research. The toolbox is designed to enable selecting the quickest and most economic tools to yield necessary datasets for decision making and modelling in this field of HC research and industrial applications (e.g., [5,42]). This concept stresses the need of valuable mineralogical input for simulators to be able to upscale from pore-to core-and field-scale.…”
Section: Discussionmentioning
confidence: 99%
“…Andersen and Berawala (2019) interpreted a vast set of experimental data to both determine reaction kinetics and the associated impact on creep compaction for Aalborg (Denmark) and Liege (Belgium) chalks. Kallesten et al (2020) extended this methodology to account for flow in compacting fractured chalk with permeability alterations in the matrix and fracture.…”
Section: Introductionmentioning
confidence: 99%
“…23 In the above review, most of the research has been conducted on whole cores to study the effect of systematically changing effective stress, temperature, and brine composition and see the resulting impact in terms of rock−fluid interactions, compaction, porosity, and permeability. Kallesten et al 29 modeled chemical creep compaction in a fractured core subject to hydrostatic stresses but concluded that more experimental data were needed to characterize the fracture. A limited number of studies have considered fractured cores, deviatoric stress, or doing repeated stress cycles.…”
Section: Introductionmentioning
confidence: 99%